2019
DOI: 10.1016/j.tim.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplexes: More Than Just a Kink in Microbial Genomes

Abstract: G-quadruplexes (G4s) are noncanonical nucleic acid secondary structures formed by guanine-rich DNA and RNA sequences. In this review we aim to provide an overview of the biological roles of G4s in microbial genomes with emphasis on recent discoveries. G4s are enriched and conserved in the regulatory regions of microbes, including bacteria, fungi, and viruses. Importantly, G4s in hepatitis B virus (HBV) and hepatitis C virus (HCV) genomes modulate genes crucial for virus replication. Recent studies on Epstein-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 101 publications
0
83
0
4
Order By: Relevance
“…In humans, they can occur in immunoglobulin switch regions, oncogene promoters, the first introns of genes, and the 5' untranslated regions near translation start sites [4,5,7,12]. These sequences also occur in bacterial genomes [13][14][15][16][17]. Reports vary as to the assessment of the potential for the participation of G-quadruplex structures in the regulation of gene expression in E. coli [13,14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, they can occur in immunoglobulin switch regions, oncogene promoters, the first introns of genes, and the 5' untranslated regions near translation start sites [4,5,7,12]. These sequences also occur in bacterial genomes [13][14][15][16][17]. Reports vary as to the assessment of the potential for the participation of G-quadruplex structures in the regulation of gene expression in E. coli [13,14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, G4s of DNA are widely distributed, conserved, and enriched in regulatory regions that perform critical functions in replication (30), transcription (31)(32)(33)(34), and translation (32). A DNA-RNA hybrid G-quadruplex formed in bacterial cells mediates transcription termination (35).…”
mentioning
confidence: 99%
“…Extensive research indicated that G-quadruplexes were involved in many critical biological processes, including DNA replication [29][30][31][32], telomere regulation [33][34][35][36][37], and RNA translation [38][39][40][41]. It has been proved that G-quadruplexes existed in the viral genome and can regulate the viral biological processes, which made it possible to function as potential drug targets for antiviral strategy [42][43][44]. A study made by Jinzhi Tan et al demonstrated that the SARS-Unique Domain (SUD) within the nsp3 (non-structural protein 3) of SARS coronavirus (SARS-CoV) exhibits the binding preference to the G-quadruplex structure in the human transcript, and potentially interfere with host cell antiviral response [45].…”
mentioning
confidence: 99%